La fortuna editoriale della Riforma di Ludovico Domenichi all'Orlando innamorato - Tedesco, Alessandro (Verbum – Analecta Neolatina, 2014)
The text aims to analyze the aspects of the editorial innovation by Ludovico Domenichi in his Reformation to the Orlando innamorato. Through an examination of the paratextual apparatuses and the changes introduced by Domenichi, the analysis aims to highlight the reasons for the success of the reform carried out by this polygraph.